Berberine and its derivatives: mechanisms of action in myocardial vascular endothelial injury - a review - Zhang, Wenhui; Guo, Siyi; Dou, Jinjin; Zhang, Xiwu; Shi, Fan; Zhang, Chun; Zhang, Huxiao; Lan, Xiaodong; Su, Yi (Frontiers in Pharmacology, 2025)
Myocardial vascular endothelial injury serves as a crucial inducer of cardiovascular diseases. Mechanisms such as endoplasmic reticulum stress, apoptosis, inflammation, oxidative stress, autophagy, platelet dysfunction, and gut microbiota imbalance are intimately linked to this condition. Berberine and its derivatives have demonstrated potential in modulating these mechanisms. This article reviews the pathogenesis of endothelial injury in myocardial vessels, the pharmacological effects of berberine and its derivatives, particularly their interactions with targets implicated in vascular endothelial injury. Furthermore, it discusses clinical applications, methods to enhance bioavailability, and toxicity concerns, aiming to lay a foundation for the development of BBR as a therapeutic agent for cardiovascular diseases.